2014
DOI: 10.1016/j.jfda.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species-related activities of nano-iron metal and nano-iron oxides

Abstract: Nano-iron metal and nano-iron oxides are among the most widely used engineered and naturally occurring nanostructures, and the increasing incidence of biological exposure to these nanostructures has raised concerns about their biotoxicity. Reactive oxygen species (ROS)-induced oxidative stress is one of the most accepted toxic mechanisms and, in the past decades, considerable efforts have been made to investigate the ROS-related activities of iron nanostructures. In this review, we summarize activities of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(124 citation statements)
references
References 69 publications
3
115
0
Order By: Relevance
“…Iron oxide (Fe 2 O 3 ) nanoparticles may be utilized in foods as colorants or sources of bioavailable iron. [47][48][49][50] The range of applications of iron oxide as a food colorant in the United States are highly limited, i.e., up to 0.1 wt% in sausages as part of casings. 51 It was estimated that the mean intake of iron oxide from consumers of these products was around 450 μg/ day.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…Iron oxide (Fe 2 O 3 ) nanoparticles may be utilized in foods as colorants or sources of bioavailable iron. [47][48][49][50] The range of applications of iron oxide as a food colorant in the United States are highly limited, i.e., up to 0.1 wt% in sausages as part of casings. 51 It was estimated that the mean intake of iron oxide from consumers of these products was around 450 μg/ day.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…53 It has been proposed that the ability of iron oxide nanoparticles to generate ROS is the most likely mechanism for their potential toxicity. 49 A study where iron oxide nanoparticles were orally administered at about 3 mg/kg body weight to rats over a 13-week period reported that they did not accumulate in tissues or produce toxicity. 54 Another rat feeding study with much higher oral dose (250-1000 mg/kg body weight) of iron oxide nanoparticles for 13-week also did not find their tissue accumulation or toxicity in both male or female rats.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most papers have described the in vitro and in vivo toxicity of chemically and/or physically synthesized iron oxide nanoparticles [32,87,90,91]. The toxicity of iron oxide nanoparticles can be attributed to the ROS induction of oxidative stress [92], and it is dependent on the particle surface, size distribution, zeta potential, and the chemical nature of the surface coating [32,87].…”
Section: Iron Oxide (Fe2o3 Fe3o4) Nanoparticlesmentioning
confidence: 99%